Z1 dependence of ion-induced electron emission from aluminum. - Alonso, E. V.; Baragiola, R. A.; Ferrón, J.; Jakas, M. M.; Oliva-Florio, A. (American Chemical Society, 1980)
Fil: Alonso, E. V. Comisión Nacional de Energía Atómica; Argentina